KEEFEKTIFAN MEDIA GAMBAR DALAM PEMBELAJARAN MENULIS TEKS PERSUASI PADA PESERTA DIDIK KELAS VIII SMP N 3 MRANGGEN TAHUN PELAJARAN 2018/2019 - Nurin Nuzulia (BASIC Jurnal Pendidikan Dasar dan Menengah, 2020)
This research aims to find out the effectiveness of picture media in learning to write persuasive texts in grade VIII students of SMP N 3 Mranggen in the 2018/2019 school year. The method used in this study is the posttest-only control design method with quantitative descriptive approach aimed to measure the improvement in writing persuasion texts in class VIII students at SMP N 3 Mranggen using image media in the form of normality test, homogeneity test, and hypothesis testing. Besides using nontes techniques in the form of documentation and student observation sheets during the learning process in class. The results obtained in this study are (1) the results of the normality test analysis; (2) homogeneity test analysis results; (3) the results of the hypothesis test analysis. Keywords: effectiveness, image media, writing persuasion textsKEEFEKTIFAN MEDIA GAMBAR DALAM PEMBELAJARAN MENULIS TEKS PERSUASI PADA PESERTA DIDIK KELAS VIII SMP N 3 MRANGGEN TAHUN PELAJARAN 2018/2019